The Validity of Electronic Contracts in Software Applications - Bambang Tri Bawono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The development of information and communication technology resulted in the form of agreements turned into electrical forms, which are commonly referred to as electronic contracts. Discussion on electronic contracts refers to Article 46 paragraph (2) President Regulation No. 71 of 2019 on the Implementation of Electronic Systems and Transactions must also fulfill the legal conditions of the agreement. Based on this case, it is necessary to do a deeper study of the electronic contract, because it certainly has the potential to not fulfill the legal conditions of the agreement.Method research used in this research is library research. While the approach in this study uses a normative juridical approach. The source of legal material in this study uses primary and secondary legal materials.The results of this study state that the validity of electronic contracts in software applications can be canceled and null and void. Electronic contracts in software applications can be canceled because they do not meet the subjective requirements in terms of skills. This is because those who make electronic contracts through click warp have the potential to be immature, because they are under 18 years of age. Especially in the context of the use of smartphones or other devices related to the use of software applications, there are no clear rules regarding the minimum limits of users of such smartphones or devices. While the electronic contract has the potential to be null and void because the electronic contract is potential to conflict with the laws and regulations of Article 47 paragraph (1) President Regulation No. 71 of 2019 on the Implementation of Electronic Systems and Transactions. Electronic contracts in software applications are generally made using foreign languages, while Article 47 paragraph (1) requires that electronic contracts faced by Indonesian citizens must be made in Indonesian.Keywords: Electronic Contracts; Click Warp Agreement; Terms of Legitimate Agreement.